Low-cost carriers versus full service carriers in ASEAN: The impact of liberalization policy on competition - Hanaoka, Shinya; Takebayashi, Mikio; Ishikura, Tomoki; Saraswati, Batari (Journal of air transport management, 2014)
This study analyses the ASEAN Single Aviation Market (ASAM) policy to be introduced by the end of 2015. We conduct a scenario study to estimate the impact of low-cost carrier (LCC) network expansion under liberalized air transport policies in the ASEAN region. Establishing joint ventures is a possible way for foreign carriers to expand the network in this region, even after starting ASAM. This is unique as joint ventures are not only subsidiaries of the full-service carriers, as is the case in the United States and Europe. We also apply a quantitative air transport market model to estimate the policy impact of the entry of new LCCs on routes from three ASEAN hub airports to Manila airport, which covers the impact on the whole network. The model produces several significant results, including that the entry of one LCC on one route may affect the fare, frequency, and profitability of related competitive routes for the entire network. •Establishing joint ventures is a possible way for foreign carriers to expand the network in ASEAN.•Model shows LCCs can match their airfare to the fare of the second leading airline, usually an FSC.•One LCC entry on one route affect the fare, frequency, and profitability across the whole network.